A tale of two uropathologists: concordance of Gleason Grade Groups in prostatic adenocarcinoma over needle biopsies and radical prostatectomies - Güner, Güneş; Kösemehmetoğlu, Kemal (Acta Medica, 2024)
Objective: The standard 12-core transrectal prostate needle biopsies don’t reflect the tumor entirely. Approximately 35-36% of needle biopsy diagnoses of Gleason grade group (GG) 1 are upgraded upon radical prostatectomy (RP). Pathologists are not in perfect concordance in Gleason scoring. Two uropathologists in a university hospital aimed to determine how concordant needle biopsy GGs were with RP GGs. Moreover, they also assessed how frequently they up-/down-graded the needle biopsy GGs each other gave when they graded RPs. Material and Methods: In-house prostate needle biopsies and RPs from 31/01/2020 to 10/09/2022 were retrieved from the hospital database. Patients who had both a needle biopsy and an RP were included. Whether each case was down-/up-graded upon RP, GGs and the pathologist that reported the cases were tabulated. Results: One hundred and thirty cases were assessed. Needle biopsy and RP GGs were identical in 63,1% (n=82). Pathologist1 (P1) assessed both the needle biopsy and RPs of 41 patients, 8 of which they downgraded and 8 upgraded (19,5%). Pathologist2 (P2) assessed both the needle biopsy and RP samples of 23 patients; downgrading 13% (n=3) and upgrading 17,4% (n=4) of cases. Where the needle biopsy was reported by P2 and RP was reported by P1 (n=48), 10 (20,8%) were downgraded and 8 (16,7%) were upgraded. The reverse scenario was noted in 18 patients; 2 (11,1%) of which were downgraded, 5 (27,8%) were upgraded. While P2 showed a tendency to upgrade more frequently, this was not statistically significant (p=0,2774, Pearson chi-square). Discussion: The two uropathologists’ up- and down-grading rates seemed concordant. Routine practice doesn’t allow time for one pathologist to re-score the other’s cases, nor is every case consulted. Looking back at pathologist-specific tendencies to up/downgrade one’s own or a colleague’s scores may help direct ourselves and others to curb tendencies to over/undergrade.